(N-Methylimidazole)(tetrahydroborato)zinc Complex as a New Stable and Efficient Reducing Agent for Reduction of Carbonyl Compounds - ZEYNIZADEH, BEHZAD; SETAMDIDEH, DAVOOD (Asian Journal of Chemistry, 2010)
(N-Methylimidazole)(tetrahydroborato)zinc complex, as a stable white solid was prepared quantitatively by complexation of an equimolar amount of zinc tetrahydroborate and N-methylimidazole at room temperature. This reagent easily reduces a variety of carbonyl compounds such as aldehydes, ketones, acyloins, α-diketones and α,β-unsaturated carbonyl compounds to their corresponding alcohols in high to excellent yields. Reduction reactions were carried out under mild conditions in acetonitrile at room temperature.